2002
DOI: 10.1081/jas-120004035
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Drug Treatment-Based Severity Measure in Childhood Asthma

Abstract: Valid measures of severity are crucial in asthma pharmacoepidemiological research. This study reports the development and validation of a severity measure in childhood asthma for application to health care administrative data. A drug treatment-based asthma severity measure was developed following the stepped care approach to treatment, and this was applied to a cohort of 16,862 children who met a case definition for asthma drug prescription use between January 1995 and March 1996. Assessments were made of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…For the proportion of each category of severity of asthma, our study found a higher proportion of mild intermittent and mild persistent asthma (91%), compared to other studies based on survey (42-76%) (42,43,47,48,76,77). This is primarily due to the fact that our study is based on a medical record review to determine asthma status and its severity of a population-based sample at the time of diagnosis of asthma.…”
Section: Discussioncontrasting
confidence: 54%
“…For the proportion of each category of severity of asthma, our study found a higher proportion of mild intermittent and mild persistent asthma (91%), compared to other studies based on survey (42-76%) (42,43,47,48,76,77). This is primarily due to the fact that our study is based on a medical record review to determine asthma status and its severity of a population-based sample at the time of diagnosis of asthma.…”
Section: Discussioncontrasting
confidence: 54%
“…Asthma status was determined by pediatric allergists' assessment in [2003][2004]. Diagnoses were made according to the Canadian Asthma Consensus Guidelines (Becker et al, 2005), whereas severity was determined based on existing classification systems (Becker et al, 2005;Kozyrskyj, Mustard, & Simons, 2002). Two boys and 5 girls had mild asthma, 5 boys and 4 girls had moderate asthma, and 4 boys and 2 girls had severe asthma.…”
Section: Participantsmentioning
confidence: 99%